Analysis of HLA-G expression in renal tissue in lupus nephritis: a pilot study. (August 2019) - Foschi, V; Bortolotti, D; Doyle, A F; Stratigou, V; Stephens, L; Trivedi, P; Rinaldi, R; Padovan, M; Bortoluzzi, A; Lightstone, L; Cairns, T D; Botto, M; et al.
Background: The study aimed to investigate whether HLA-G antigen is expressed in the kidneys of patients affected by lupus nephritis (LN) and whether its detection in renal biopsies could be adopted as a marker of treatment response and prognosis. Methods: Thirty renal biopsies from patients with LN were selected and analyzed through immunohistochemistry. Laboratory and clinical data were retrospectively collected at baseline, 6 and 12 months and at the latest clinical appointment. A number of patients (63.3%) were treated with rituximab (RTX) +/− methylprednisolone in the induction phase. The expression of HLA-G in glomeruli, tubules and infiltrating cells was examined and compared between lupus patients who achieved either complete or partial renal response and those who did not respond to treatment. Results: HLA-G staining was observed in the glomeruli of 20 of 30 samples from patients with LN. The expression of the antigen was detected in podocytes, along glomerular capillary walls, on parietal glomerular epithelial cells and within the juxtaglomerular apparatus. Seventy per cent of patients whose glomeruli expressed HLA-G achieved partial or complete response at 6 months and 75% at the latest available follow up compared with 30% and 40%, respectively, of those who did not show any expression. The pattern of staining in tubules and infiltrating cells was highly variable precluding any clinical correlation. Conclusion: This study demonstrates that HLA-G is expressed in renal tissue in LN. Our retrospective data suggest that its expression could correlate with response to treatment.